2018
DOI: 10.1111/apt.14673
|View full text |Cite
|
Sign up to set email alerts
|

Letter: serum HBcrAg is a useful marker for disease monitoring, predicting treatment response and disease outcome of chronic hepatitis B virus infection

Abstract: Linked content This article is linked to Mak et al and Mak and Yuen papers. To view these articles visit https://doi.org/10.1111/apt.14376 and https://doi.org/10.1111/apt.14684.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Compared to serum HBsAg and HBV DNA level, serum HBcrAg had a better correlation with intrahepatic cccDNA 17 . Evidence is accumulating that HBcrAg could predict the response to NAs therapy, off‐treatment viral relapse, HBeAg seroconversion and the risk of development to HCC 18 . Wang and colleagues revealed that the quantitative serum HBsAg and HBcrAg could predict the HBeAg seroconversion in HBeAg‐positive patients treated with NAs 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to serum HBsAg and HBV DNA level, serum HBcrAg had a better correlation with intrahepatic cccDNA 17 . Evidence is accumulating that HBcrAg could predict the response to NAs therapy, off‐treatment viral relapse, HBeAg seroconversion and the risk of development to HCC 18 . Wang and colleagues revealed that the quantitative serum HBsAg and HBcrAg could predict the HBeAg seroconversion in HBeAg‐positive patients treated with NAs 19 …”
Section: Introductionmentioning
confidence: 99%
“…17 Evidence is accumulating that HBcrAg could predict the response to NAs therapy, off-treatment viral relapse, HBeAg seroconversion and the risk of development to HCC. 18 Wang and colleagues revealed that the quantitative serum HBsAg and HBcrAg could predict the HBeAg seroconversion in HBeAg-positive patients treated with NAs. 19 It has been reported that correlation between new markers (HBcrAg and HBV RNA) and HBeAg clearance or seroconversion is better than that of the traditional markers (HBsAg and HBV DNA).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, early on‐treatment serum HBcrAg level was found to be a good biomarker for predicting off‐treatment HBeAg seroconversion in patients receiving peginterferon therapy, and as compared to serum HBsAg level, serum HBcrAg has a better correlation with intrahepatic cccDNA . In addition, patients with low HBcrAg and HBsAg levels are also reported to have a low relapse risk after cessation of antiviral therapy …”
Section: Introductionmentioning
confidence: 99%
“…6,9 In addition, patients with low HBcrAg and HBsAg levels are also reported to have a low relapse risk after cessation of antiviral therapy. 10,11 Recently, serum HBV RNA is also attracting attention as a useful biomarker. 12,13 As early as 1996, serum HBV RNA was identified in HBV-infected patients but its nature and origin were unclear until recently when serum HBV RNA was confirmed to be pregenomic RNA (pgRNA).…”
Section: Introductionmentioning
confidence: 99%
“…7 In past decade, many studies suggested that monitoring the baseline and early on-treatment levels of serum HBsAg and HBcrAg would also help to reflect intrahepatic cccDNA levels and predict viral relapse risk after cessation of nucleotide analogs (NAs). [9][10][11] Additionally, serum HBsAg levels could be used to evaluate the treatment of already available agents (such as pegylated interferon and NAs) whether should be optimized or adjusted. 12,13 Unfortunately, correlations between serum HBV pgRNA, HBsAg, and HBcrAg levels are rarely head-to-head compared, and it is still unclear whether these viral serum markers can be replaced by each other.…”
mentioning
confidence: 99%